Agent-based simulation of emergency response to plan the allocation of resources for a hypothetical two-site major incident. (November 2015) - Hawe, Glenn I.; Coates, Graham; Wilson, Duncan T.; Crouch, Roger S.
Abstract: During a major incident, the emergency services work together to ensure that those casualties who are critically injured are identified and transported to an appropriate hospital as fast as possible. If the incident is multi-site and resources are limited, the efficiency of this process is compromised as the finite resources must be shared among the multiple sites. In this paper, agent-based simulation is used to determine the allocation of resources for a two-site incident which minimizes the latest hospital arrival times for critically injured casualties. Further, how the optimal resource allocation depends on the distribution of casualties across the two sites is investigated. Such application supports the use of agent-based simulation as a tool to aid emergency response.